A Critical Review of Mechanisms of Tax Information Exchange Agreements - Vahid Asadzadeh; Seyed Ghasem Zamani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The principle of information flow, also known as the exchange of information, has been recognized in the field of international tax law and tools and mechanisms have been considered for its realization including the mechanisms of tax information exchange agreements. With the globalization of the international tax law, taxpayer activities are no longer limited to a specific Border, but still the tax administration needs to be restricted to their borders. Therefore, governments need more cooperation with each other and to this end, the exchange of tax information in various forms, including exchange-to-demand, automatic exchange, and spontaneous exchange of information through the conclusion of bilateral and multilateral international treaties is possible. This article critically reviews the tax information exchange agreements. The descriptive and analytical methods can be used to enter into an appropriate document to set up the exchange of information agreement between countries with different systems of income tax had hoped.